ChemInform Abstract: 1D Coordination Polymers with Polychalcogenides as Linkers Between Metal Atoms. Issue 33 (25th July 2013) - Kysliak, Oleksandr; Beck, Johannes
Abstract Compounds (III), (IV), (VI), and (IX) are solvothermally synthesized in liquid NH3 or MeNH2 and characterized by single crystal XRD, Raman, and diffuse reflectance spectroscopy.